Can the Full-Percutaneous Endoscopic Lumbar Discectomy in Day Surgery Mode Achieve Better Outcomes Following Enhanced Recovery after Surgery Protocol? A Retrospective Comparative Study - Kou, Le; Wan, Wentao; Chen, Chao; Zhao, Dong; Sun, Xun; Gao, Ziwei; Wu, Hongjin; Di, Mingyuan; Ma, Xinlong; Xu, Baoshan; Miao, Jun; Wang, Zheng; et al. (Frontiers in Surgery, 2022)
Objective: To analyze whether F-PELD in day surgery mode following ERAS can produce better clinical outcomes than in traditional surgery mode. Methods: The patients who underwent F-PELD between January 2019 and October 2020 were retrospectively analyzed, and the patients who met the inclusive criteria were followed up. The patients were divided into day surgery (DS) group (n=152) that combined with ERAS and traditional surgery (TS) group (n=123) without ERAS. The length of hospital stays (LOS), visual analogue scale (VAS), and Oswestry Disability Index (ODI) of two groups were compared before surgery, immediately after surgery, one month after surgery, and one year after surgery. Results: A total of 298 patients who underwent F-PELD were reviewed. 290 patients were included in the study and followed up, and 275 patients who had completed the follow-up were available for analysis. There were no statistically significant differences between the two groups in terms of age, gender, preoperative VAS, and ODI. There were significant statistical differences in the VAS and ODI immediately after surgery (VAS for back pain: DS group 1.4±1.1, TS group 2.0±1.2, P<0.001; VAS for leg pain: DS group 0.8±0.8, TS group 1.1±1.1, P=0.010; ODI: DS group 5.8±4.3, TS group 7.6±7.4, P=0.010) and one month after surgery (VAS for back pain: DS group 0.8±0.9, TS group 1.1±1.0, P=0.035; ODI: DS group 3.2±3.5, TS group 4.5±6.5, P=0.036). At one year after surgery, the VAS (back pain: DS group 0.3±0.6, TS group 0.3±0.7, P<0.798; leg pain: DS group 0.2±0.4, TS group 0.1±0.4, P=0.485) and ODI (DS group 0.8±1.2, TS group 0.7±1.7, P=0.729) were further improved, but no statistically significant difference was observed between two groups. LOS of DS group (1.38±0.49 days) was significantly shorter than the DS group (5.83±2.24 days, P <0.001), and some postoperative complications occurred in the TS group, including throat discomfort (n=5, 4.1%), discomfort after catheterization (n=7, 5.7%), abdominal distention (n=3, 2.4%), and nausea (n=5, 4.1%). None of the above complications resulted in serious consequences. Conclusion: The F-PELD in day surgery mode following ERAS produced a better short-term clinical effect and reduced the LOS, which is worthy of promotion.